2020
DOI: 10.1016/j.mayocpiqo.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Acute Kidney Injury and Its Effect on Mortality in Patients Hospitalized From COVID-19

Abstract: Objective To determine the incidence of and risk-factors for development of acute kidney injury (AKI) and investigate the association between AKI and mortality in patients hospitalized with Covid-19. Patients and Methods This retrospective case series includes the first 370 patients consecutively hospitalized with confirmed Covid-19 illness between March 10, 2020 and May 13, 2020, at a 242-bed teaching hospital. To determine independent association between demographic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 21 publications
13
71
2
8
Order By: Relevance
“…Data from the America and England reported on the disparities in the risk and outcomes of COVID-19, with a higher risk in black people than white people [22,23]. Nimkar et al also demonstrated African-American race showed higher odds of AKI than the White [11]. However, our study indicated patients in White with COVID-19 had a signi cant increase in risk for AKI, whereas the pooled OR revealed a non-signi cant increase in Black.…”
Section: Publication Biascontrasting
confidence: 68%
See 3 more Smart Citations
“…Data from the America and England reported on the disparities in the risk and outcomes of COVID-19, with a higher risk in black people than white people [22,23]. Nimkar et al also demonstrated African-American race showed higher odds of AKI than the White [11]. However, our study indicated patients in White with COVID-19 had a signi cant increase in risk for AKI, whereas the pooled OR revealed a non-signi cant increase in Black.…”
Section: Publication Biascontrasting
confidence: 68%
“…Finally, 11 studies (6, 9-18) with 8815 patients with COVID-19 ful lled eligibility criteria (Fig 1). Table 1 presents the summary characteristics of the 11 included studies [6,[9][10][11][12][13][14][15][16][17][18]. The prevalence of AKI ranged from 10.3% to 81%.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published studies on AKI in COVID- 19 have thus far been hindered by relatively small sample sizes or incomplete clinical courses with patients still receiving treatment in the hospital. [7][8][9][10] As recovery from COVID-19, especially when severe, often takes weeks in the hospital, previously published studies may result in a skewed view of endpoints, potentially biasing toward adverse outcomes. [11][12][13] Additionally, prior publications have not addressed varied timelines of AKI development during hospitalization or the varied duration of follow-up.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%